2009
DOI: 10.1016/j.concog.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Semantic and subword priming during binocular suppression

Abstract: In general, stimuli that are familiar and recognizable have an advantage of predominance during binocular rivalry. Recent research has demonstrated that familiar and recognizable stimuli such as upright faces and words in a native language could break interocular suppression faster than their matched controls. In this study, a visible word prime was presented binocularly then replaced by a high-contrast dynamic noise pattern presented to one eye and either a semantically related or unrelated word was introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(154 citation statements)
references
References 35 publications
(52 reference statements)
8
145
1
Order By: Relevance
“…Except for a study by Costello et al (2009) that used the aid of a visible prime presented for 2 s, existing studies have not yet demonstrated semantic processing in the suppressed phase during binocular rivalry. Zimba and Blake (1983) presented the prime word during suppression or during dominance and found shorter lexical decision RTs for semantically related words (i.e., a semantic priming effect) only during dominance phases of rivalry.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Except for a study by Costello et al (2009) that used the aid of a visible prime presented for 2 s, existing studies have not yet demonstrated semantic processing in the suppressed phase during binocular rivalry. Zimba and Blake (1983) presented the prime word during suppression or during dominance and found shorter lexical decision RTs for semantically related words (i.e., a semantic priming effect) only during dominance phases of rivalry.…”
Section: Discussionmentioning
confidence: 94%
“…Following the two most relevant studies using CFS (Costello et al, 2009;Jiang et al, 2007), we also performed a manipulation check to ensure that the result obtained was not caused by response bias -different criteria used for different kinds of critical stimuli after but not during the interocular suppression phase. In this control experiment, the critical stimulus was superimposed on the Mondrians, and both were projected into two eyes, thus changing the viewing from dichoptic to binocular.…”
Section: Methodsmentioning
confidence: 99%
“…They found that a consciously presented prime did not affect participants' behavioral responses to a CFS-masked word, but did affect the N400 ERP component -although only when participants' attention was directed away from that suppressed word. Eo et al argue that this feature -focusing attention away from the suppressed stimulus -may account for studies in which semantics affects CFS suppression times (as in Sklar et al, 2012 as well as Costello et al, 2009 andYang &Yeh, 2011), because in those studies participants did not know the location of the suppressed stimulus and could not attend to it. However, participants in our experiments also did not know the location of the suppressed stimuli, and yet showed no evidence that they had accessed the meanings of those stimuli.…”
Section: The Potential For False Positives In the Breaking Cfs Paradigmmentioning
confidence: 99%
“…For example, semantic information can be processed without awareness and break through binocular suppression (Costello et al 2009), although it is unclear how much semantic information can be processed whilst undergoing dichoptic suppression (Zimba and Blake 1983). Organising local image features like lines and angles into letters, and subsequently letters into words, must require fairly sophisticated processing.…”
Section: Unconscious Perceptual Organisationmentioning
confidence: 99%